PROPOSTA DE UM SISTEMA PARA COLETA DE DADOS DE ACIDENTES DO TRABALHO EM EMPRESAS - SCHNEIDER, ANDRESA; SACKSER, GILBERTO; DUARTE, LUIZ C. S.; RIBEIRO, LUÍS F. M.; ECKHARDT, MOACIR (Salão do Conhecimento, 2013)
Resumo